Electrical stimulation to optimize cardioprotective exosomes from cardiac stem cells. (March 2016) - Campbell, C.R.; Berman, A.E.; Weintraub, N.L.; Tang, Y.L.
Abstract: Injured or ischemic cardiac tissue has limited intrinsic capacity for regeneration. While stem cell transplantation is a promising approach to stimulating cardiac repair, its success in humans has thus far been limited. Harnessing the therapeutic benefits of stem cells requires a better understanding of their mechanisms of action and methods to optimize their function. Cardiac stem cells (CSC) represent a particularly effective cellular source for cardiac repair, and pre-conditioning CSC with electrical stimulation (EleS) was demonstrated to further enhance their function, although the mechanisms are unknown. Recent studies suggest that transplanted stem cells primarily exert their effects through communicating with endogenous tissues via the release of exosomes containing cardioprotective molecules such as miRNAs, which upon uptake by recipient cells may stimulate survival, proliferation, and angiogenesis. Exosomes are also effective therapeutic agents in isolation and may provide a feasible alternative to stem cell transplantation. We hypothesize that EleS enhances CSC-mediated cardiac repair through its beneficial effects on production of cardioprotective exosomes. Moreover, we hypothesize that the beneficial effects of biventricular pacing in patients with heart failure may in part result from EleS-induced preconditioning of endogenous CSC to promote cardiac repair. With future research, our hypothesis may provide applications to optimize stem cell therapy and augment current pacing protocols, which may significantly advance the treatment of patients with heart disease.